IMPLEMENTATION OF THE SELF ORGANIZED LEARNING ENVIRONMENT (SOLE) LEARNING MODEL TO IMPROVE STUDENT’S LEARNING OUTCOMES IN ACCOUNTING AT SMK KOPERASI YOGYAKARTA IN THE ACADEMIC YEAR OF 2022/2023 - Cheryl Clairine Salsabila; Ani Widayati (Jurnal Pendidikan Akuntansi Indonesia, 2023)
This research aims to improve Student Accounting Learning Outcomes using the Self Organized Learning Environment (SOLE) learning model. This research is a type of classroom action research with a quantitative approach. This research was conducted in two cycles consisting of four stages, namely planning, action, observation, and reflection. The research subjects were students of class XI AKL at SMK Koperasi Yogyakarta in the Academic Year 2022/2023. Data collection techniques used were tests (pre-tests and post-test) and field notes. The result obtained from this study shows that the Accounting Learning Outcomes has increased. A comparison of the average values of the post-test and pre-test in each cycle. The average values of the pre-test in cycle I is 48.24, increases to 72.94 in the post-test or increase by 24.70. In cycle II, the average pre-test score is 46.67, rising to 78 in the post-test or increase by 31.33. Class Classical Completeness in the pre-test cycle I of 5.88% increases to 58.82% in the post-test or an increase of 52.94%. In cycle II, the Classical Class Completeness of the pre-test learning outcomes is 20%, rises to 80% in the post-test or increasing by 60%. It can be concluded applying the Self Organized Learning Environment (SOLE) Learning Model can improve the Accounting Learning Outcomes of Class XI AKL Students in SMK Koperasi Yogyakarta. Keywords: Learning outcomes, SOLE, Learning Model